COMPARATIVE EVALUATION OF CONVENTIONAL PAP SMEAR AND LIQUID-BASED CYTOLOGY FOR CERVICAL CANCER SCREENING IN A CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To compare liquid-based cytology (LBC) and conventional Pap smear (CPS) in the detection of cervical cancer.Study Design: This was a cross-sectional study.Place and Duration of Study: This research was conducted at Liaquat University of Medical and Health Sciences Jamshoro from February 2025 to February 2026Methods: Total 200 women aged 20-65 years with symptomatic presentation indicative of cervical pathology were included. CPS and LBC were used to collect cervical samples. Smear adequacy, endocervical cell presence, and cytological findings were assessed. Histopathological findings were used as a reference standard where available. SPSS version 26 was used to analyze the data. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were computed. The p-value of